2019
DOI: 10.1016/j.cell.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF-1 Drives PERIOD Synthesis to Entrain Circadian Rhythms with Feeding Time

Abstract: Summary In mammals, endogenous circadian clocks sense and respond to daily feeding and lighting cues, adjusting internal ∼24 h rhythms to resonate with, and anticipate, external cycles of day and night. The mechanism underlying circadian entrainment to feeding time is critical for understanding why mistimed feeding, as occurs during shift work, disrupts circadian physiology, a state that is associated with increased incidence of chronic diseases such as type 2 (T2) diabetes. We show that feeding-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
218
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(233 citation statements)
references
References 91 publications
(125 reference statements)
13
218
1
1
Order By: Relevance
“…Circadian rhythms regulate CCGs in a tissue-specific manner throughout the body 53 . Circadian rhythms in peripheral organs are affected by numerous inputs including light 54,55 , nutrients 22,56,57 , and systemic cues from SCN [58][59][60][61][62] . Previous studies characterizing CCGs in different organs from in vivo mice uncovered organ-specific regulation of circadian rhythms integrated by both peripheral clocks and systemic cues from SCN.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythms regulate CCGs in a tissue-specific manner throughout the body 53 . Circadian rhythms in peripheral organs are affected by numerous inputs including light 54,55 , nutrients 22,56,57 , and systemic cues from SCN [58][59][60][61][62] . Previous studies characterizing CCGs in different organs from in vivo mice uncovered organ-specific regulation of circadian rhythms integrated by both peripheral clocks and systemic cues from SCN.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unlikely that its circadian rhythm will dictate IGF-I signaling to orexin neurons. Rather, it seems more plausible that brain and physical activity 24,25 , and/or feeding schedule 26 will modulate orexin activity, since all these situations are accompanied by increased brain IGF-I input. But more work is needed to determine the specific cues timing IGF-I input to orexin neurons.…”
Section: Discussionmentioning
confidence: 99%
“…ECG segments of 5 minutes were analyzed with this software using the Fast Fourier Transform algorithm to obtain the power spectra. The mean power density was calculated for 5 different frequency bands that constitute the global ECG: delta band (0.3-5 Hz), theta band (5-8 Hz), alpha band (8-12 Hz), beta band (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz), and gamma band . The total power of the five frequency bands was considered 100%, and the percentage of each frequency band was calculated for the 60 minutes.…”
Section: Electrocorticogram (Ecg) Recordings In Freely Moving Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic nuclear receptor TFs are important modulators of liver circadian networks, as demonstrated by HNF4A ChIP‐seq in mouse livers, which showed that binding of this TF to chromatin is rhythmic (Qu et al, ). Liver metabolic pathways, such as insulin signaling, are also involved in circadian rhythm regulation (Crosby et al, ; E. E. Zhang et al, ), indicating that the relationship between clock and metabolism is bidirectional. This notion has been further corroborated by studies describing global changes of circadian transcriptional and epigenomic landscapes in diet‐induced obesity models (Eckel‐Mahan et al, ; Kohsaka et al, ).…”
Section: Liver Enhancer Dynamicsmentioning
confidence: 99%